Rancang Bangun Aplikasi Penentuan Kelayakan Pemberian Pinjaman Kepada Pensiun Menggunakan Metode Weighted Product - Kezia Tirza Naramessakh; Cahyo Prianto (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
In supporting the operation of PT. Pos Indonesia, one of which is offering retirees such as pension savings and pension credit. Credit is the provision of money or bills based on an agreement or loan agreement between a company and another party. In providing pension credit, it must be accurate and accurate for retirees who are entitled or eligible to get a loan. So the author makes an application to determine the feasibility of lending in order to make it easier to determine which retirees are eligible to be given a credit loan. This study uses the Weighted Product (WP) method, which is one method of decision making. By using the Weighted Product method can help in making lending decisions by doing a ranking process that will determine the best alternative from retirees. The author uses five criteria, namely, the amount of salary, loan amount, age, credit period, and what credit. The application of determining the feasibility of lending to pensions is based on a website using the code igniter framework. For designing or modeling this application uses UML (Unified Modeling Language). This research resulted in an application that helped in determining a proper pension to be given a pension loan using Weighted Product.